English Medieval Misericords The Margins of Meaning - Hardwick, Paul 1960- (Boydell Studies in Medieval Art and Architecture, 2011)
A comprehensive survey of the intriguing misericord carvings, setting them in their religious context and looking at their different themes and motifs